METODE PENDIDIKAN AKHLAK PADA ANAK USIA 15-18 TAHUN DALAM BUKU ISLAMIC PARENTING KARYA SYAIKH JAMAL ABDURRAHMAN - Aqmi Hanavami (Fakutas Tarbiyah Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2015)
This research is based on the importance of the moral education method from parents to their children which refers to the Islamic Parenting Book. In order for moral education to run in accordance with Islamic religious principle, parents to need understand ad pay attention to the main components in moral education. Of the many references that discuss the method moral education for children aged 15-18 years, the Islamic Parenting book by Syaikh Jamal Abdurrahman is an interesting reading source to be studied more deeply, because it contains more method of child moral education so that it can be a reference for parents and teacher. The purpose of this study was to describe and analyze 1) The concept of moral education for children aged 15-18 years in the book Islamic Parenting by Syaikh Jamal Abdurrahman. 2) The method of moral education for children aged 15-18 years in the book Islamic Parenting by Syaikh Jamal Abdurrahman. This study uses a qualitative approach that is literature study (Library Research) with the type of text or document study. The data collection technique uses document analysis while the data analysis technique uses content analysis. The result of this study indicate that the concept of moral education for 15-18 years-old is a) Luqmanul Hakim’s message to students of knowledge, b) Al-Ghazali’s message to students of knowledge, c) wisdom to guide virtue, d) the child’s self and property belong to his father. The method of moral education for children aged 15-18 years is a) encouraging children to make profits early in the morning, b) maintaining aspecs of children skill’s, tendencies and talents, c) instiling love for the prophet, his family and friends as well as love for the Koran, d) instilling an independent attitude and hard work, e) strengthening children’s right to study and learning the Koran, f) choosing a pious teacher, g) ordering girls to waer the hijab when they reach puberty, h) instilling trustworthiness and responbility, i) advise children by praising them first so that they are more effective, j) teach children to be filial and ethical to parents, k) entrust important tasks to children, l) make prophets as an example.